Discussion of stainless steels for surface condensers and feedwater heater tubing. (Nickel Institute, 2020)
This publication, in two parts, is for design engineers, utility metallurgists and chemists, and those concerned with the best design and most efficient operation of large surface condensers and feedwater heaters. The text in Part One covers the condenser operating environment in which tube materials must perform, and it describes the use of stainless steel condenser tubes to combat problems that arise in such an environment. Part Two discusses the use of stainless steel for feedwater heater tubing. The booklet provides design and engineering data, which can be helpful for the engineer approaching stainless steel for the first time, or as a review for those experienced in its use.
"Originally, this handbook was published in 1974 by the Committee of Stainless Steel Producers, American Iron and Steel Institute. The Nickel Institute republished the handbook in 2020."
Keywords: Condensers (Steam); Feed-water heaters.; Stainless steel.; elektronické knihy; electronic books